Revision of the Megasoma (Megasoma) gyas (Jablonsky in Herbst, 1785) species group (Coleoptera, Scarabaeidae, Dynastinae) - Massimo Prandi; Paschoal C. Grossi; Fernando Z. Vaz-de-Mello (ZooKeys, 2020)
The taxa of the genus Megasoma Kirby, 1825 (Coleoptera, Scarabaeidae, Dynastinae) related to M. gyas (Jablonsky in Herbst, 1785) are revised. Megasoma (M.) gyas is recognized as a monotypic species restricted to the Caatinga biome of northeastern Brazil. Megasoma gyas rumbucheri Fischer, 1968, is considered as a new synonym of M. gyas. The “long-horned M. gyas” is recognized as a separate polytypic species M. (M.) typhon (Olivier, 1789) with the nominative subspecies occurring through the Mata Atlântica biome of Brazil, from Bahia to São Paulo states and M. (M.) typhon prandii Milani, 2008 restricted to a small area in the state of Santa Catarina, South Brazil. Megasoma gyas porioni Nagai is considered as a new synonym of M. typhon typhon. The “short-horned M. gyas” occurring in Minas Gerais, São Paulo, and southwestern Bahia, is recognized as a separate new species and described as M. (M.) hyperion sp. nov. The paper includes an historical research and the redescriptions of the other nominal species of the genus. Distribution maps and a key to species in the M. (M.) gyas species group (males and females) are also provided.